Pajak Penghasilan 26 : Analisis dan Pemahaman untuk Wajib Pajak Luar Negeri - Nabila Nasywa; Wa Ode Jeslin (Pajak dan Manajemen Keuangan, 2025)
Article 26 of the Indonesian Income Tax Law (PPh Pasal 26) is a significant fiscal regulation that imposes withholding tax on income derived from Indonesian sources and received by foreign taxpayers who do not have a permanent establishment (PE) in Indonesia. The implementation of this regulation plays a crucial role in securing state revenue from cross-border transactions while also addressing the issue of double taxation through Double Taxation Avoidance Agreements (DTAAs). Income subject to PPh 26 includes dividends, interest, royalties, rent, service fees, rewards, pensions, and insurance premiums. The standard withholding tax rate is 20% of the gross or estimated net income, although lower rates may apply depending on applicable tax treaties. The calculation method varies depending on the type of income and the existence of a DTAA. This article also highlights the importance of determining the beneficial owner in applying tax treaty benefits, as well as the challenges faced by companies and tax authorities in enforcement. A case study is presented to illustrate how PPh 26 is calculated on insurance and reinsurance transactions involving foreign entities. Understanding the mechanism, rates, and legal context of PPh 26 is essential for taxpayers and practitioners to ensure compliance and mitigate potential tax disputes.